2018
DOI: 10.1098/rsos.180008
|View full text |Cite
|
Sign up to set email alerts
|

Phoretic interactions and oscillations in active suspensions of growing Escherichia coli

Abstract: Bioluminescence imaging experiments were carried out to characterize spatio-temporal patterns of bacterial self-organization in active suspensions (cultures) of bioluminescent Escherichia coli and its mutants. An analysis of the effects of mutations shows that spatio-temporal patterns formed in standard microtitre plates are not related to the chemotaxis system of bacteria. In fact, these patterns are strongly dependent on the properties of mutants that characterize them as self-phoretic (non-flagellar) swimme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…E. coli can produce millimolar concentrations of indole from tryptophan by means of tryptophanase (TnaA) during the stationary growth phase under nutrient-rich conditions 16 . The ability of indole to be excreted into the extracellular medium is strong and indole has good volatility, thus the growth rate of E. coli can be selectively enhanced by gentle agitation to increase the signal response of indole for targeted analysis, regulated by numerous pathways that typically connect growth to nutrient availability (free tryptophan) 21 . Thus, the enhancement of indole emission during the early culture time of bacteria is particularly beneficial for the rapid identification of E. coli .
Figure 4Time profiles of indole signal ( m/z 116) detected by CDI-MS from the headspace of simulated blood cultures with different initial concentrations of E. coli (negative ionization mode).
…”
Section: Resultsmentioning
confidence: 99%
“…E. coli can produce millimolar concentrations of indole from tryptophan by means of tryptophanase (TnaA) during the stationary growth phase under nutrient-rich conditions 16 . The ability of indole to be excreted into the extracellular medium is strong and indole has good volatility, thus the growth rate of E. coli can be selectively enhanced by gentle agitation to increase the signal response of indole for targeted analysis, regulated by numerous pathways that typically connect growth to nutrient availability (free tryptophan) 21 . Thus, the enhancement of indole emission during the early culture time of bacteria is particularly beneficial for the rapid identification of E. coli .
Figure 4Time profiles of indole signal ( m/z 116) detected by CDI-MS from the headspace of simulated blood cultures with different initial concentrations of E. coli (negative ionization mode).
…”
Section: Resultsmentioning
confidence: 99%
“…Let us finally mention that, to explain pattern formation in experiments with E. coli bacteria in which chemotaxis plays no role [164], the authors of reference [164] have suggested that phoretic interactions might also play a role for bacteria. Clearly, this far-reaching suggestion calls for further explorations.…”
Section: Measurementsmentioning
confidence: 99%
“…Let us finally mention that, to explain pattern formation in experiments with E.coli bacteria in which chemotaxis plays no role [163], the authors of ref. [163] have suggested that phoretic interactions might also play a role for bacteria. Clearly, this far-reaching suggestion calls for further explorations.…”
Section: Cross-interactionsmentioning
confidence: 99%